VIRTUAL WEB PROMOSI DAN RESERVASI HOTEL BERBASIS WEB DAN VIA SMS PADA HOTEL DIAMOND - Setiawan, Alexander; ., Yulia; Kurnia, Andrie (Institute of Research and Community Outreach - Petra Christian University, 2012)
Web and SMS is a new development that is useful for many people as a data exchange media. In the business world, especially for marketing use, by using those two media business can be performed globally so that informations are fast and easily spread all over the world. From this problem born an idea to promote Diamond Hotel by using web and a facility to reserve room using SMS. This Application was created by using VB 6 language and using AT command to communicate with cellphone. Meanwhile, data that flow between system and cellphone are in the form of Protocol Data Unit. System had been tested by sending SMS request from a cellphone and system sent back SMS response as requested by user.